A Pilot Program Assessing Bronchoscopy Training and Program Initiation in a Low-income Country. Issue 2 (April 2021) - Siddharthan, Trishul; Jackson, Peter; Argento, A. Christine; Sachdeva, Ashutosh; Yarmus, Lonny; Alupo, Patricia; Kirenga, Bruce; Woordria, William; Lee, Hans J.
Abstract : Background: Flexible bronchoscopy is an essential procedure for the evaluation and management of the pulmonary disease. However, this technology and related training is not available in many low-middle income countries (LMICs). We conducted a pilot training program for flexible bronchoscopy in Uganda. Methods: A multimodal curriculum was developed with pulmonologists from Uganda and the United States. The training included an online distance learning management system for video content, simulation, just-in-time training, and deliberate practice via clinical proctoring. Procedural standards and a de novo bronchoscopy suite were concurrently developed. Competency was assessed using the Bronchoscopic Skills and Tasks Assessment Tool written examination and the Ontario Bronchoscopy Assessment Tool. Results: We trained 3 pulmonary physicians with no prior experience in flexible bronchoscopy. Three bronchoscopies with bronchoalveolar lavage were performed during the training and an additional 11 cases were performed posttraining. All 3 Ugandan physicians had an increase in their written Bronchoscopic Skills and Tasks Assessment Tool and Ontario Bronchoscopy Assessment Tool in the competent range ( P <0.05). All bronchoscopies were successfully completed, adequate samples were obtained, and there were no procedure-related complications. Conclusion: Bronchoscopy implementation in LMICs is feasible, but requires competency-based training. Further studies are needed to validate this curriculum in LMICs, including the use of this type of curriculum for more complicated bronchoscopic procedures.